Uji Ketahanan Bakteri Asam Laktat (BAL) Terhadap Asam Pada Eco-Enzyme Kulit Buah Jeruk - Hajrah Hidriya; Yuliana Salman; Muhammad Zaini (HB PRESS, 2025)
Eco enzyme is a fermented product from organic waste that has an impact on health and the environment. Eco enzyme is fermented from leftover fruit peels mixed with water and molasses sugar for approximately 90 days. One of the fruit peels that can be used as an eco-enzyme product is orange peel. This study aims to determine the number of germs and test the bacterial resistance to acid in eco enzyme orange peel. The study used a quantitative descriptive method. The sample in this study, namely eco enzyme orange peel that is 90 days old, was calculated the number of germs using a multilevel dilution method, then a bacterial resistance test was carried out to acid in a regulated acidic environment, namely in acidic environmental conditions. Based on the LAB resistance test isolated from eco enzyme to low pH, it showed that 4 LAB isolates with gram-positive properties and rod-shaped can survive in media conditions with a pH of 0.8-2.5 LAB that is faced with more acidic conditions is increasingly resistant to the environmental conditions, this is indicated by the presence of sediment at the bottom of the tube and turbidity after the incubation process for 24 hours. So the eco enzyme can be developed as a probiotic.